KETERAMPILAN BERPIKIR KREATIF SISWA DALAM MEMBENTUK BANGUN DATAR DI SDN BERANGAS 2 BARITO KUALA - Rahmah, Aulia; Darmiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze activities, creative thinking skills, and student learning outcomes in carrying out mathematics learning in broad flat material using Project Based Learning, Group Investigation, and Course Review Horay. This research was carried out using a qualitative and quantitative approach with 4 meetings in class V of SDN Berangas 2 for the 2023/2024 academic year with a total of 32 students. The research instruments used teacher activity observation sheets, student activity observation sheets, student creative thinking skills observation sheets, and student learning outcomes. The results of the research showed that the increase in teacher activity at meeting I was 75% (good), meeting II was 78.5% (good), meeting III was 83.5% (very good), and meeting IV was 90% (very good), the increase in student activity at meeting I was 56.25% (quite active), meeting II 71.88% (active), meeting III 87.5% (very active), and meeting IV 90.63% (very active), increasing students' creative thinking skills at meeting I by 37.5% (less creative), meeting II 62.5% (creative), meeting III 78.13% (creative), and meeting IV 87.5% (very creative), and student learning outcomes at meeting I achieved KKTP at 50%, meeting II 68.75%, meeting III 84.37%, and at the IV meeting it increased to 90.63% who achieved KKTP. Based on the research results, it was concluded that the Project Based Learning model combined with Group Investigation and Course Review Horay can significantly increase activity, creative thinking skills and student learning outcomes.